EFFECT OF ETHANOL EXTRACT FROM MALACCA LEAVES (Phyllanthus emblica) ON THE SPERM QUALITY OF MICE - Thasmi, Cut Nila; Asmilia, Nuzul; Suryani, Elfi Satria; Hafizuddin, Hafizuddin; Adam, Mulyadi; Sayuti, Arman; Nazaruddin, Nazaruddin; Panjaitan, Budianto (Jurnal Kedokteran Hewan, 2022)
This study aims to analyze the effect of administering Malacca leaves (Phyllanthus emblica) extract on the sperm quality of mice. This leaf extract was administered orally using gavage method once daily for 21 days. There were four treatment groups: the control group (P0) received distilled water while the first (P1), second (P2), and third (P3) treatment groups received 300 mg, 600 mg, and 1200 mg of Malacca leaf ethanol extract/kg body weight, respectively. Each groups consisted of four mice and was evaluated for sperrm motility, viability, morphology, and concentration. The results showed that sperm motility, viability, morphology and sperm concentration tended to decrease after administration of Malacca leaf ethanol extract for all parameters, although there was no significant difference (P0.05). It was concluded that the administration of Malacca leaf ethanol extract tends to reduce the sperm quality of mice. ___________________________________________________________